If you need to solve for `x` the given expression, you need to convert it into an equation such that:

`-6x^2 + (sqrt3)x^2 = 0`

You need to factor out `x^2` such that:

`x^2(-6 + sqrt3) = ` 0

You need to divide by`-6 + sqrt3` such that:

`x^2 = 0 => x_1 = x_2 = 0`

**Hence, evaluating the solutions to the equation `-6x^2 + (sqrt3)x^2 = 0` yields `x_1 = x_2 = 0.` **

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now